2022
DOI: 10.3390/biomedicines10061300
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pulmonary Embolism in COVID-19: A Potential Connection between Venous Congestion and Thrombus Distribution

Abstract: Background: Vascular abnormalities, including venous congestion (VC) and pulmonary embolism (PE), have been recognized as frequent COVID-19 imaging patterns and proposed as severity markers. However, the underlying pathophysiological mechanisms remain unclear. In this study, we aimed to characterize the relationship between VC, PE distribution, and alveolar opacities (AO). Methods: This multicenter observational registry (clinicaltrials.gov identifier NCT04824313) included 268 patients diagnosed with SARS-CoV-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…found a pulmonary embolism incidence of 25% in hospitalized patients ( 7 ), while a systematic literature search identified in 27 studies with 3,342 patients a prevalence of 16.5% in all patients scanned for COVID-19 ( 9 ). Recently, Nevesny et al ( 17 ) highlighted a potential connection between pulmonary embolism and venous congestion in the affected territories without arterial dilatation ( 17 ). More importantly, Nevesny et al demonstrated that vascular congestion primarily happens in the venous compartment in COVID-19 pneumonia, with normal caliber veins in the non-affected zones, directing the discussion of pathophysiology towards specific mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…found a pulmonary embolism incidence of 25% in hospitalized patients ( 7 ), while a systematic literature search identified in 27 studies with 3,342 patients a prevalence of 16.5% in all patients scanned for COVID-19 ( 9 ). Recently, Nevesny et al ( 17 ) highlighted a potential connection between pulmonary embolism and venous congestion in the affected territories without arterial dilatation ( 17 ). More importantly, Nevesny et al demonstrated that vascular congestion primarily happens in the venous compartment in COVID-19 pneumonia, with normal caliber veins in the non-affected zones, directing the discussion of pathophysiology towards specific mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Images were acquired with the following parameters: rotation speed, 0.5 s; voltage, 80/140 kVp; tube load, 249 to 485 mAs; reconstructed slice thickness, 1.25 mm; and section interval, 1 mm; 80 keV. 60 to 100 mL (depending on patient’s size and weight at the discretion of the radiology technician in charge) of iodinated contrast material (Accupaque 300 ® , GE Healthcare, Oslo, Norway) were injected intravenously followed by a saline chaser ( 17 , 25 ). All exams were acquired to enhance both pulmonary and systemic vessels, using the bolus tracking technique to trigger the acquisition as per routine protocols applied in the department.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations